'S13‐1955C': A high‐yielding conventional soybean with high oil content, multiple disease resistance, and broad adaptation. Issue 2 (29th April 2021) - Chen, P.; Shannon, G.; Scaboo, A.; Crisel, M.; Smothers, S.; Clubb, M.; Selves, S.; Vieira, C. C.; Ali, M. L.; Lee, D.; Nguyen, H. T.; Li, Z.; et al.
Abstract: The conventional Maturity Group V soybean [ Glycine max (L). Merr.] cultivar 'S13‐1955C' (Reg. no. CV‐540, PI 695317) was developed and released by the University of Missouri–Fisher Delta Research Center soybean breeding program in 2019. Plants of S13‐1955C have determinate growth habit, white flowers, tawny pubescence, tan pod wall, and seed with black hilum. It has high oil content (227.4 g kg −1 ) and broad disease resistance including soybean cyst nematode, southern root‐knot nematode, reniform nematode, sudden death syndrome, and frogeye leaf spot. S13‐1955C was tested in 177 environments across 13 states and averaged 101% of the check yield in Missouri and the southern states from 2014 to 2019. Core Ideas: S13‐1955C is a conventional soybean with flexibility and premium prices. It has broad disease resistance, providing yield security when exposed to multiple diseases. It combines seed quality traits, a good disease package, and high yield performance. Stability and adaptability shown by consistent yield performance across 177 environments.